2016
DOI: 10.1186/s12935-016-0328-z
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-135a promotes hepatocellular carcinoma cell migration and invasion by targeting forkhead box O1

Abstract: AimsHepatocellular carcinoma (HCC) is the third leading cause of cancer mortality worldwide. Many microRNAs (miRNAs), small non-coding RNAs, are involved in regulating cancer cell proliferation, metastasis, migration, invasion and apoptosis.Main methodsWe investigated the expression of miR-135a in HCC cell lines and clinical tissues. The effect of miR-135a on migration and invasion of HepG2 and MHCC-97L were examined using wound healing and Transwell assay. We determined the expression of miR-135a, forkhead bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…High miR-135a levels favour invasive and metastatic growth of HCC cells in vitro and are correlated with malignant portal vein thrombosis, possibly by directly targeting MTSS1 [20]. Other targets of miR-135a investigated in vitro are forkhead box O1, matrix metalloproteinase-2, AKT pathway, and Krüppel-like factor-4 [21, 22]. Therefore, from a functional perspective, elevated levels of miR-135a might induce early formation of microscopic HCC dissemination via several pathways, and thus, result in early HCC recurrence after curative resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High miR-135a levels favour invasive and metastatic growth of HCC cells in vitro and are correlated with malignant portal vein thrombosis, possibly by directly targeting MTSS1 [20]. Other targets of miR-135a investigated in vitro are forkhead box O1, matrix metalloproteinase-2, AKT pathway, and Krüppel-like factor-4 [21, 22]. Therefore, from a functional perspective, elevated levels of miR-135a might induce early formation of microscopic HCC dissemination via several pathways, and thus, result in early HCC recurrence after curative resection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Liu et al showed that overexpression of miR-135a favours an invasive and metastatic behaviour of HCC in vitro and is associated with malignant portal vein thrombosis in vivo, most likely by directly targeting metastasis suppressor 1 (MTSS1) [20]. Two other studies showed that miR-135a also down-regulates Krüppel-like factor 4, up-regulates the expression of matrix metalloproteinase-2 and Akt, and down-regulates forkhead box O1, resulting in higher proliferation and invasiveness of HCC cells [21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…MiR-135a reportedly enhances cellular proliferation in multiple malignancies, including colorectal cancer [33], hepatocellular carcinoma [34], and melanoma [35]. It also purportedly promotes tumour formation in bladder cancer and suppresses p21 expression [26].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, cell proliferation is suppressed in HCC due to let-7a and let-7 g that regulates the oncogenic STAT3 and cMyc, respectively [42]. miRNA-135a targets fork-head box O1 and miRNA-155-3p suppresses FBXW7 leading to an increased invasion and migration in HCC [56, 153]. miRNA-186 targets Yes-associated protein 1 and acts as a potential therapeutic target in treating HCC [48].…”
Section: Noncoding Rnasmentioning
confidence: 99%